Prevalence, Pathogen Profiles, and Antibiotic Resistance Patterns of Pediatric Urinary Tract Infections: A Retrospective Analysis at Almotrod General Hospital, Libya - Baha Ettrmal; Reda Tronba; Sahar Beshna; Sumia Dra (AlQalam Journal of Medical and Applied Sciences, 2025)
Urinary tract infections (UTIs) remain one of the most common bacterial infections in childhood. This two-year retrospective study analyzed the prevalence, causative organisms, and antibiotic resistance patterns among pediatric patients admitted to Almotrod General Hospital in Libya between August 2023 and August 2025. A total of 1,420 urine samples were analyzed, with 82 (5.8%) culture-positive cases. Escherichia coli was the predominant organism (64.6%), followed by Klebsiella spp. (17.1%) and Proteus spp. (12.2%). Resistance was highest to ampicillin and co-trimoxazole, while nitrofurantoin and amikacin remained the most effective antibiotics. Continuous local surveillance and rational antibiotic use are essential to guide empirical therapy for pediatric UTIs.